FINANCIAL INCLUSION AND INCOME INEQUALITY IN WEST AFRICA - Eze, Emeka; Chukwuma-Ogbonna, Joyce; Ogbonna, Chukwuma (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
The study investigated the effect of financial inclusion on inequality in West Africa. The study used data from 13 West African countries for which data were available. Data on Gini coefficient, human development index, financial inclusion index, per capita income, government expenditure, inflation, dependency ratio, mean school years, voice and accountability and trade openness was used in the analysis. Also, the study constructed a financial inclusion index using data on credit to the private sector, Number of bank brancher per 100000 of the population and bank account ownership per thousand of the population. Empirically, the study applied Panel OLS Panel Fixed effect and Panel Random effect estimators to evaluate the objectives of the study. Evidence from the study indicate that Financial inclusion has a negative relationship with inequality in West Africa, however the effect of financial inclusion on inequality reduction was found to be insignificant indicating that financial inclusion may have marginal effect at best on inequality in the West Africa Sub region. The findings from the study has some policy implications. Firstly, the negative but insignificant effect of financial inclusion on income inequality may have resulted from low levels of financial inclusion in West Africa. This implies that at higher levels of financial inclusion, the effect may become more pronounced.